2020
DOI: 10.3390/cancers12040861
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin-Sle A Glycoforms as E-Selectin Ligands and Potentially Targetable Biomarkers at the Cell Surface of Gastric Cancer Cells

Abstract: Background: Gastric cancer (GC) is a major health burden worldwide, with half of patients developing metastases within 5 years after treatment, urging novel biomarkers for diagnosis and efficient therapeutic targeting. Sialyl-Lewis A (SLeA), a terminal glycoepitope of glycoproteins and glycolipids, offers tremendous potential towards this objective. It is rarely expressed in healthy tissues and blood cells, while it is present in highly metastatic cell lines and metastases. SLeA is also involved in E-selectin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 78 publications
0
47
0
Order By: Relevance
“…Moreover, activation of other B3GALT genes, as reported in prostatic cancer [89], cannot be excluded. Very recently, an unusual carrier of sLea with potential therapeutic relevance has been detected in gastric cancer cell lines [90], which deserves confirmation in native tissues. We suggest that the future use of Lewis antigens as tumor markers should be based on knowledge of their expression pattern in native cancers and related normal tissues, as well as in nonmalignant diseases of the same organs.…”
Section: Ca199 Lea and Leb In Colon Cancer And Other Gastrointestimentioning
confidence: 88%
“…Moreover, activation of other B3GALT genes, as reported in prostatic cancer [89], cannot be excluded. Very recently, an unusual carrier of sLea with potential therapeutic relevance has been detected in gastric cancer cell lines [90], which deserves confirmation in native tissues. We suggest that the future use of Lewis antigens as tumor markers should be based on knowledge of their expression pattern in native cancers and related normal tissues, as well as in nonmalignant diseases of the same organs.…”
Section: Ca199 Lea and Leb In Colon Cancer And Other Gastrointestimentioning
confidence: 88%
“…Despite mounting evidence that NCL is a valid therapeutic target in different types of aggressive cancer [ 29 , 32 , 57 , 59 , 60 ], the data for PCa are lacking. In the present study we aimed to demonstrate that targeting surface NCL by the scFv 4LB5 is an effective way to inhibit multiple neoplastic features of PCa cells.…”
Section: Discussionmentioning
confidence: 99%
“…A protein involved in miRNA regulation, nucleolin (NCL), is expressed predominantly in the nucleolus in normal cells [ 18 ] and is known to participate in a multitude of different cellular processes [ 19 , 20 , 21 ]. In cancer cells, NCL becomes aberrantly overexpressed [ 22 , 23 ], translocated to the cell membrane [ 24 , 25 ], and participates in several cancer-driving activities [ 26 , 27 , 28 , 29 , 30 , 31 ] including biogenesis of oncogenic miRNAs such as miR-21, -103, -221, and -222 [ 32 ]. NCL has been shown to exhibit similar cellular behavior in PCa, and exhibits greater surface expression in CRPC cell lines than in hormone-naïve models [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Addressing alterations in the glycosylation of membrane proteins holds a great potential towards this objective [8]. In fact, over the past years, we and other research groups have demonstrated that changes in the structure and distribution of glycans in proteins at the surface of cancer cells may provide the necessary bispecificity towards unique cancer molecular signatures [8,9]. Namely, we have identified MUC16, CD44 and nucleolin glycoforms holding potential for more accurate patient stratification and treatment follow-ups in different types of tumors [9][10][11].…”
Section: Introductionmentioning
confidence: 99%